Using radiotracers and topographic metrics for sediment budgeting at pixel and hillslope scales: A case study from western Iran - Reza Zarei; Abdulvahed Khaledi Darvishan; Paolo Porto; Mohammad Reza Zare (Ecological Indicators, 2024)
Topographic variables play important roles not only on soil erosion, but also on sediment redistribution inside the watersheds, both of which can be studied using radiotracer of 137Cs. In this regard, the current research aims to establish a sediment budget using ecological indicators of topographic metrics and radiotracers and to examine the relationship between topographic metrics and the sediment budget components in two scales of pixel and hillslope. To achieve the study purposes, soil erosion and redistribution map was prepared based on 137Cs method and work units’ approach in the 102.14 ha control sub-watershed of Khamsan representative watershed, western Iran. Then, the 1-m digital elevation model was used to extract the topographic metrics. The sediment budget components including total erosion, total deposition, net erosion and sediment delivery ratio and topographic metrics including slope angle, slope length, profile curvature, plan curvature, stream power index, topographic wetness index and flow accumulation were calculated for 14 selected hillslopes. The results showed that land use dominates the rate of erosion and sedimentation of the watershed in the long term (60–70 years). Out of 526.87 t y−1 of erosion occurred in the study sub-watershed, only 20.26 t y−1 were redistributed within the watershed, and 506.61 t y−1 were delivered to the watershed outlet and the specific net erosion was calculated at the rate of 5.05 (t/ha y−1). The amount of erosion and sedimentation was noticeably affected by the reduction of the slope angle and changing rangelands to agriculture in the lower part of the slopes. At the pixel scale, the LS, slope angle and stream power index had significant positive correlations of 0.57, 0.60 (sig. < 0.01) and 0.39 (sig. < 0.05) with the rate of erosion and sedimentation, respectively. In the hillslope scale, with the decrease of the slope angle down the slopes, the intensity of erosion increased due to the land use change from rangeland to rainfed agriculture in the downslopes. Therefore, land use change to agriculture on lower slopes exacerbates soil erosion, emphasizing the need for targeted land management practices.